Trend Penelitian terkait Digital Preservasi Naskah Kuno : A Bibliometric Analysis on SCOPUS (2012-2022) - Fandi Rahman Hidayat; Tamara Adriani Salim; Frans Asisi Datang; Muhammad Prabu Wibowo (Media Pustakawan, 2023)
Bibliometric analysis is a quantitative method for analyzing data in existing databases at journal publishers. This method is used to find out how much a particular topic has been researched and discussed by researchers in the field concerned. This method is to find out current research trends and what types of research are still lacking and need to be explored more deeply for future needs regarding digital preservation of ancient library manuscripts. The data presented comes from existing analysis drawn from the SCOPUS Journal database and then the data is also processed through the VOSviewer application. In the research trends regarding digital preservation that exist in this modern era, it is considered important to know the trends and directions of research related to this issue, especially as we currently live in a fast-paced modern world. This is also because we are in the digital era and digital preservation has become an important topic to discuss in recent years. Various kinds of challenges and opportunities are very interesting to discuss regarding the research topic of digital preservation of manuscripts in libraries.